Uniform Domains and Uniform Domain Decomposition Property in Real Normed Vector Spaces - Huang, M.; Wang, X. (MATHEMATICA SCANDINAVICA, 2013)
Let $E$ be a real normed vector space with $\dim(E)≥ 2$, $D$ a proper subdomain of $E$. In this paper we characterize uniform domains in $E$ in terms of the uniform domain decomposition property. In addition, we discuss the relation between quasiballs and domains with the quasiball decomposition property in $\mathsf{R}^n$.